RANTAI PEMASARAN KANGKUNG DI DESA TATELI SATU KECAMATAN MANDOLANG KABUPATEN MINAHASA (Water Spinach Marketing Chain in Tateli Satu Village, Mandolang District, Minahasa Regency) - Yudia Lahopang; Theodora M. Katiandagho; Juliana R. Mandei (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to determine the pattern of marketing channels,to  analyze the costs, profits and marketing margins at each level of the marketing channel and to find out the farmer's share at each level of the marketing channel. This research was conducted from October 2021 to December 2021 in Tateli Satu Village, Mandolang District. The data used in this study were primary data and secondary data. then analyzed descriptivelyThe results showed that the marketing channel formed on the marketing of water spinach in Tateli Satu village consisted of three forms of marketing channels, namely marketing channel 1 (farmer - village collector – consumer); marketing channel 2 (farmers - village collector - retailer – consumer) and marketing channel 3 (farmers - wholesalers – consumers).The highest marketing costs, profits and margins was in marketing channel 1, which was IDR 28,314.81 or 18.27 percent. The highest profit was in marketing channel 2, which was IDR 115,414.48 or 55.40 percent. The highest marketing margin was in marketing channel 2, which was IDR 113,333 or 54.40 percent. The share received by the farmer generated in marketing channel 3 was the highest one compared to the share received in the marketing channels 1 and 2.